2017
DOI: 10.1177/0971685816673484
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Workplace Spirituality on Knowledge Sharing Intention: A Conceptual Framework

Abstract: Knowledge forms a crucial source for gaining competitive advantage and its sharing a dominant challenge facing several organizations. In this paper we propose a positive role of workplace spirituality (WPS) (at individual and collective levels) on knowledge sharing intention (KSI) by employing the theory of decomposed planned behaviour. We argue that WPS with its focus on inner spirit, meaningful work, sense of interconnectedness and alignment with organizational values and mission positively strengthens an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 65 publications
1
22
1
Order By: Relevance
“…Although the review of Radaelli et al (2015) aimed to support the micro-foundation of knowledge sharing by identifying determinants of willingness to share based on TPB, this study paid attention to physicians’ knowledge sharing behaviour in hospitals in top tier and specialist journals. Tsai et al (2012) and Khari and Sinha (2017) reviewed TPB and TRA from the social psychological perspectives and knowledge sharing. While these studies develop a conceptual framework to identify the antecedents of TRA and TPB, TRA and TPB were not systematically reviewed and trends of modifications of TRA and TPB have not been shown.…”
Section: Introductionmentioning
confidence: 99%
“…Although the review of Radaelli et al (2015) aimed to support the micro-foundation of knowledge sharing by identifying determinants of willingness to share based on TPB, this study paid attention to physicians’ knowledge sharing behaviour in hospitals in top tier and specialist journals. Tsai et al (2012) and Khari and Sinha (2017) reviewed TPB and TRA from the social psychological perspectives and knowledge sharing. While these studies develop a conceptual framework to identify the antecedents of TRA and TPB, TRA and TPB were not systematically reviewed and trends of modifications of TRA and TPB have not been shown.…”
Section: Introductionmentioning
confidence: 99%
“…This topic is worth investigating because it may enable hospital and spiritual caregivers to understand and incorporate these factors and the findings in this research into policies and practices for enhanced spiritual healthcare provision. A recent research reported that shared spiritual values enable the caregiver and patient to give a new dimension to spiritual care (Khari and Sinha 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Spiritual climate refers to organizational contextual readiness and conduciveness to foster spirituality (Khari & Sinha ). It is the shared perception of the employees towards spirituality and the state and process of sharing spirituality in the workplace.…”
Section: Introductionmentioning
confidence: 99%